Local Culture-Based Two-Dimensional Visual Arts Learning through Batik Training at Rumah Tuo Rantau Panjang - Febra Muyusari; Endang Komara; Teti Ratna Wulan (Pascasarjana Institut Seni Indonesia Padang Panjang, 2026)
This study examines local culture-based two-dimensional visual arts learning through batik training at the cultural heritage site of Rumah Tuo Rantau Panjang, Merangin Regency, Jambi Province. Previous studies have discussed batik, local wisdom, and visual arts education separately; however, research that specifically positions a cultural heritage site as an authentic learning space for two-dimensional visual arts through batik training remains limited, particularly in the context of Jambi Malay culture. This study aims to describe and analyze how batik training at Rumah Tuo Rantau Panjang functions as a contextual, participatory, and culturally grounded model of visual arts learning. The research employed a qualitative approach with a descriptive case study design. Data were collected through participatory observation, semi-structured interviews, and documentation involving elementary school students, university students, teachers, community members, batik artisans, site managers, and local cultural figures. The data were analyzed using the interactive model of Miles, Huberman, and SaldaÃ±a through data condensation, data display, and conclusion drawing. The findings show that batik training in Rumah Tuo Rantau Panjang provides meaningful visual arts learning experiences by integrating artistic practice, cultural interpretation, and direct engagement with local heritage. Participants improved their understanding of Jambi Malay batik motifs, technical skills in batik making, visual composition, and cultural appreciation. The motifs taught, including Keluk Paku, Tampuk Manggis, Tali Ikat, Mensinding Gulung Paku, and Akar Kekait, embody philosophical values related to leadership, kinship, social boundaries, and customary traditions. This study contributes to the development of local culture-based art education by proposing cultural heritage sites as authentic learning laboratories. The novelty lies in integrating batik training, cultural site-based learning, and two-dimensional visual arts education within the specific context of Rumah Tuo Rantau Panjang.